A REVIEW ON THE APPLICATION OF NANOTECHNOLOGY IN THE TREATMENT OF HYPERTENSION - Vamshi Krishna Tippavajhala (Journal of Global Pharma Technology, 2017)
Hypertension or elevated blood pressure is a common chronic disease. It is associated with severe symptoms like aneurysms, chronic kidney disease, amnesia, improper speech, blindness, peripheral artery disease, brain stroke, heart attack etc. Pathophysiology for hypertension involves the role of autonomous nervous system, cardiac output and renin-angiotensin aldosterone system. This review article mainly deals with the application of nanotechnology and nanoparticulate drug delivery systems in the formulation of various antihypertensive drugs for the treatment of hypertension. Applications of various nanoparticulate drug delivery systems like solid lipid nanoparticles, polymeric nanoparticles, nanosuspensions and self-nanoemulsifying drug delivery systems for antihypertensive drugs have been reviewed and discussed in this article which indicate that the bioavailability of various poorly soluble and permeable antihypertensive drugs can be improved using these nano carriers.